2015
DOI: 10.1088/2040-8978/17/3/035504
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of Airy–Gaussian beam in Kerr medium

Abstract: By using the method of moments, the critical power of the Airy–Gaussian (AiG) beam is given for different decay factors and different distribution factors numerically. The critical power Pcr of the AiG beam decreases as the distribution factor increases. Using the split-step Fourier method, the propagations of the AiG beam in the free space and in the Kerr medium are shown. It has been found that the self-acceleration effect becomes weaker when the distribution factor increases. As the initial input power incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…In 2004, Bandres et al [18] and López-Mariscal et al [19] have analyzed the features of the nondiffracting parabolic beams theoretically and experimentally, respectively. Many studies have been interested in the properties of pseudo-nondiffracting beams through other optical systems such as Kerr media [20] [21], and crystals [22] [23]. Airy beams which are regarded as the zeroth-order Olver beams attract the attention of a lot of scientists of the laser community [24]- [30].…”
Section: Introductionmentioning
confidence: 99%
“…In 2004, Bandres et al [18] and López-Mariscal et al [19] have analyzed the features of the nondiffracting parabolic beams theoretically and experimentally, respectively. Many studies have been interested in the properties of pseudo-nondiffracting beams through other optical systems such as Kerr media [20] [21], and crystals [22] [23]. Airy beams which are regarded as the zeroth-order Olver beams attract the attention of a lot of scientists of the laser community [24]- [30].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the spatial solitons can be steadily transmitting in the (1 þ 1)D local Kerr medium when the nonlinear effect balances the diffraction effect. Generally speaking, for an AiG beam, the initial field distribution is [18]:…”
Section: Basic Theorymentioning
confidence: 99%
“…They have found that the momentum of the analytical AiG beam solution of the SnyderMitchell model is not conservational and obtained the quasi-AiryGaussian soliton in the Gaussian-shaped response material. Chen et al have exhibited the propagation of AiG beam in Kerr Medium [18]. Their study has showed that the self-acceleration effect of the AiG beam becomes weaker when the distribution factor increases and as the initial input power increases, they observe the quasibreather finally.…”
Section: Introductionmentioning
confidence: 99%
“…An AiG beam carrying finite power maintains the nondiffracting propagation properties within a finite propagation distance, and can be realized experimentally to a very good approximation. To date, analytical vectorial structure [24] and propagation in a quadratic-index medium [25], in the fractional fourier transform plane [26], in Kerr medium [27] and through slabs of right-handed materials and left-handed materials [28] of an AiG beam have been reported. What is more, Ez-Zariy et al have studied propagation characteristics of an AiG beam passing through a misaligned optical system with finite aperture [29].…”
Section: Introductionmentioning
confidence: 99%